2007
DOI: 10.1111/j.1467-839x.2007.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Placing age differences in the context of the Orissa supercyclone: Who experiences psychological distress?

Abstract: The present study examines the influence of age on anxiety, depression, and post-traumatic stress of the supercyclone-affected people in Orissa. The data were collected in structured interview sessions 3 months after the disaster struck. Of the 130 interviewees, 65 persons were severely exposed and the rest were mildly exposed to the supercyclone. When the effects of exposure, caste, and gender were controlled, linear effects of age on psychological distress were found to be significant, whereas quadratic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Culture plays a significant role in psychological processes (Prince and Davies 2007). Suar, Mishra and Khuntia (2007) noted an example of its role in generating psychological distress after the Orisa cyclone in India in 1999. In the region, they argued that people are like gardeners who expand their family tree and, as they approach their deaths, hope to see all their family members happy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture plays a significant role in psychological processes (Prince and Davies 2007). Suar, Mishra and Khuntia (2007) noted an example of its role in generating psychological distress after the Orisa cyclone in India in 1999. In the region, they argued that people are like gardeners who expand their family tree and, as they approach their deaths, hope to see all their family members happy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an earthquake can put older people at high risk of their lives for many reasons (Chou et al 2003), such as the death of their spouse or children (Murphy et al 2003), physical health problems (Qin, Agerbo and Mortensen 2003) and lack of income (Petrovich et al 2001). Studies have found that older people have a great need for social support during a disaster to mitigate the effects of stress (Fernandez et al 2002) and following a disaster are among those most vulnerable to psychological distress (Suar, Mishra and Khuntia 2007; Hess 2004 b ). Iran's health system provided a planned mental health intervention in Bam, and around 51 per cent of the affected population were covered by the programme eight months after the earthquake (Akbari et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The EU requires that member states forbid discrimination on grounds of gender, age, disability, sexuality, race/ethnicity and religion (Krizhan et al 2013). Although our research has focused mainly on gender differences, within the disasters' literature, there is enough evidence to show that gender, along with other diversities, in particular age and disability, and other contextual vulnerabilities can lead to different intersecting gendered experiences (Agustin, 2013;Krizhan et al 2013;Wilson, 2006;Suar et al 2007;Twigg et al, 2011;Help Age International, 2013;Help Age International, 2014;Help Age International/Age andDisability Consortium, 2015, Kelman andStough, 2015).…”
Section: Discussion and Conclusion: Mainstreaming Gender And Diversimentioning
confidence: 99%
“…These high-risk groups have been categorized in a variety of ways, including by geography, 1 ethnicity, 2 and age. 3 Older adults in particular are frequently highlighted as a subpopulation requiring specific attention or care. The 2008 UK Cabinet Office report "Identifying People Who Are Vulnerable in a Crisis" recognizes 13 vulnerable groups including older people, 4 and the United Kingdom's national adaptation plan for climate change has a particular focus on measures to mitigate the expected effects of changes in the climate on these groups, and in particular the elderly.…”
mentioning
confidence: 99%
“…Disasters and public health events broadly affect communities and societies as a whole, but they also carry specific risks and outcomes for particular population groups. These high-risk groups have been categorized in a variety of ways, including by geography, 1 ethnicity, 2 and age 3 . Older adults in particular are frequently highlighted as a subpopulation requiring specific attention or care.…”
mentioning
confidence: 99%